APLIKASI BERBASIS MULTIMEDIA UNTUK PEMBELAJARAN HARDWARE KOMPUTER - Putri, Nency Extise (STKIP PGRI Sumatera Barat, 2015)
Interactive applications for the introduction of computer hardware specification is built using Macromedia Flash 8. With this application, is expected to assist in identifying the computer hardware. Where with this application will be easier to recognize the shape and functions of each computer hardware. Introduction of computer hardware application contains information about the type and characteristics of any hardware connected to the computer. This application contains multimedia elements such as maps, images, text, and also the sound made by interactive so as easy to use. issues discussed was the introduction of computer hardware specifications ranging from application design, manufacture of hardware elements, pictures, text, and sound, action script programming, until the application can be run.